(untitled) (Revista de Ciências Agroveterinárias, 2019)
The seed germination and the early plant growth of corn (Zea mays) and soybean (Glycine max) sowed after cropping and under straw residues (simulating crop rotations) of oat (Avena sativa), ryegrass (Lolium multiflorum) and wheat (Triticum aestivum) were investigated in pot experiments carried out under controlled conditions. The germination rates ranged from 78 to 95% (corn) and from 68 to 97% (soybean), while the speed emergence index ranged from 0.9 to 1.3 (corn) and from 0.7 to 0.12 (soybean). The lowest germination rates and speed emergence indexes occurred in crop rotation for wheat (corn) and ryegrass (soybean). In addition, the highest seedling emergence average time occurred in the crop rotation for wheat (corn) and ryegrass (soybean). On the other hand, the crop rotation for oat affected neither the speed emergence index nor the seedling emergence average time, despite causing a slight reduction of the seed germination (corn and soybean) and the shoot length (corn). Except for the crop rotation for ryegrass (soybean), the total dry mass of corn and soybean reduced when winter crops were previously cultivated. These results suggest that a delay and a reduction of seed germination and seedling emergence can occur in subsequent summer crops, depending on the winter species previously cropped, impacting on the early growth of summer crops.